Close to me [videorecording (DVD)] - Samuels, Michael; Pell, Angela; Nielsen, Connie, 1965-; Eccleston, Christopher; Lynch, Susan, 1971-; Best, Leanne, 1980-; Blood, Nick, 1982-; Taylor, Tom, 2001-; McEwen, Rosy; Jensen, Henning, 1943-; Reynolds, Amanda, 1965- (Sundance Now, 2022)
Jo Harding is a woman who has a perfect life with her partner until a fall erases an entire year from her memory. As she struggles to piece events together, Jo discovers that her life was, in fact, far from perfect.